From miRNA sponges to mTOR blockades: mapping the multidimensional landscape of ameloblastoma pathogenesis and precision targeting - Mao, Jingsong; Gai, Qingxuan; Bao, Xinling; Zhong, Ming (Frontiers in Oncology, 2025)
BackgroundAmeloblastoma is a benign but locally aggressive odontogenic tumor with frequent recurrence after conservative surgery. Evidence accumulated since 2010 implicates dysregulated non-coding RNAs (ncRNAs)—notably microRNAs (miRNAs) and circular RNAs (circRNAs)—as higher-order regulators of oncogenic signaling.ObjectiveThis study aimed to synthesize peer-reviewed mechanistic and translational evidence on ncRNA networks in ameloblastoma, with explicit grading by evidence tier and emphasis on druggable nodes.MethodsWe conducted a structured narrative search of PubMed, Scopus, and Web of Science (January 2010–May 31, 2025) using controlled terms for “ameloblastoma,” “microRNA,” “circRNA,” and key pathways (MAPK, PI3K–Akt–mTOR, Wnt/β-catenin, IL-33/STAT3; Hippo/YAP–TAZ considered contextually). Peer-reviewed studies with experimental validation in ameloblastoma were prioritized, while purely computational predictions and unrelated tumor entities were excluded.ResultsAcross patient tissues, cell models, and limited in vivo studies, recurrent miRNA changes—i.e., loss of miR-524-5p, miR-141-3p, and miR-1-3p and gain of miR-29a-3p—converge on MAPK/ERK and PI3K–Akt–mTOR signaling. Loss of miR-524-5p derepresses IL-33/ST2, amplifying NF-κB/STAT3 and PI3K signaling (preclinical). miR-29a-3p targets CTNNBIP1 to reinforce Wnt/β-catenin (preclinical). miR-141-3p is anti-migratory and has been reported to upregulate NCAM1 in ameloblastoma models (preclinical). miR-1-3p restrains LAMP2-mediated autophagy (preclinical). Overexpressed circRNAs (e.g., circ-MAP3K7 and circ-HIPK3) can titrate tumor-suppressive miRNAs and sustain pathway activity (preclinical). No randomized clinical trials in ameloblastoma exist to date.ConclusionsA coherent ncRNA network appears to maintain druggable signaling convergence in ameloblastoma. Translation will require multicenter validation of the ncRNA biomarkers, early-phase trials testing rational MAPK–mTOR combinations with ncRNA modulation, and jaw-targeted delivery approaches. Claims herein are limited to peer-reviewed, ameloblastoma-relevant evidence.